Applying MATLAB to Radar Systems Modeling - Svyd, I.V.; Sierikov А.О.; Obod, I.I. (Radiotekhnika, 2022)
The paper demonstrates the important role of using radar systems in many spheres of human activity to solve complex and important problems of society. The paper examines and analyzes the capabilities of the MATLAB program package applying to the design, modernization and research of radar systems. The analysis performed shows that the MATLAB software package is a powerful tool for modeling, researching and designing radar systems for various purposes. Also, attention is paid to the MATLAB Radar Toolbox, which includes a wide range of available models that can be modified. The Radar Toolbox provides rapid modeling, upgrading and prototyping of standard and upgraded radar systems. Using the MATLAB to research radar systems is impossible without understanding the principles of construction and operation of radar systems. It is also necessary to know the features of using the MATLAB function to describe, present and model structural elements and processes in radar systems. The paper presents the main functionality and possible options for implementing models in the MATLAB for modeling and studying radar systems. The given list of model options is not exhaustive and final and can be expanded and supplemented depending on specific tasks and requirements for implementation.